Proteins, Pathologies and Politics Dietary Innovation and Disease from the Nineteenth Century - Gentilcore, David C.; Smith, Matthew (Bloomsbury Academic, 2018)
Proteins, Pathologies and Politics presents an international and historical approach to dietary change and health, contrasting current concerns with how issues such as diabetes, cancer, vitamins, sugar and fat, and food allergies were perceived in the 19th and 20th centuries. Though what we eat and what we shouldn't eat has become a topic of increased scrutiny in the current century, the link between dietary innovation and health/disease is not a new one. From new fads in foodstuffs, through developments in manufacturing and production processes, to the inclusion of additives and evolving agricultural practices changing diet, changes often promised better health only to become associated with the opposite. With contributors including Peter Scholliers, Francesco Buscemi, Clare Gordon Bettencourt, and Kirsten Gardner, this collection comprises the best scholarship on how we have perceived diet to affect health. The chapters consider: - the politics and economics of dietary change - the historical actors involved in dietary innovation and the responses to it - the extent that our dietary health itself a cultural construct, or even a product of history This is a fascinating and varied study of how our diets have been shaped and influenced by perceptions of health and will be of great value to students of history, food history, nutrition science, politics and sociology.